Restriction and sequence alterations affect DNA uptake sequence-dependent transformation in Neisseria meningitidis. - Ole Herman Ambur; Stephan A Frye; Mariann Nilsen; Eirik Hovland; Tone Tønjum (PLoS ONE, 2012)
Transformation is a complex process that involves several interactions from the binding and uptake of naked DNA to homologous recombination. Some actions affect transformation favourably whereas others act to limit it. Here, meticulous manipulation of a single type of transforming DNA allowed for quantifying the impact of three different mediators of meningococcal transformation: NlaIV restriction, homologous recombination and the DNA Uptake Sequence (DUS). In the wildtype, an inverse relationship between the transformation frequency and the number of NlaIV restriction sites in DNA was observed when the transforming DNA harboured a heterologous region for selection (ermC) but not when the transforming DNA was homologous with only a single nucleotide heterology. The influence of homologous sequence in transforming DNA was further studied using plasmids with a small interruption or larger deletions in the recombinogenic region and these alterations were found to impair transformation frequency. In contrast, a particularly potent positive driver of DNA uptake in Neisseria sp. are short DUS in the transforming DNA. However, the molecular mechanism(s) responsible for DUS specificity remains unknown. Increasing the number of DUS in the transforming DNA was here shown to exert a positive effect on transformation. Furthermore, an influence of variable placement of DUS relative to the homologous region in the donor DNA was documented for the first time. No effect of altering the orientation of DUS was observed. These observations suggest that DUS is important at an early stage in the recognition of DNA, but does not exclude the existence of more than one level of DUS specificity in the sequence of events that constitute transformation. New knowledge on the positive and negative drivers of transformation may in a larger perspective illuminate both the mechanisms and the evolutionary role(s) of one of the most conserved mechanisms in nature: homologous recombination.